Family Puzzle: Fragmentation and Repetition in Quiénes somos ahora, by Katya Adaui - Campaña Fimbres, Jesús Adalberto (2025)
Katya Adaui's (1977) narrative work has some common aspects, such as both formal and thematic fragmentation in tune with complex family relationships. Quienes somos ahora (2022), her most recent novel, is no exception to the Peruvian author's aesthetic tendencies. The writer deploys an extremely interesting construction that is oriented towards hybridization with the axes of family relationships, through the constant instrumentalization of two main resources: fragmentation and repetition that repeatedly reorients the suggested themes with a language in continuous dialogue with poetry. This article aims to investigate the implications of fragmentation and repetition, whose use represents in different ways the complex relationship of the main character with her mother. Scenes will be analyzed with emphasis on the resources available in the narrative, whose concern for forms is a pillar within the narrative fabric, in addition to reconstructing a complex and fractured relationship. This reconstruction brings together the rubble in the relationship between mother and daughter that the narrator and main character of Quienes somos ahora carries with them.